Pandangan Alkitab Tentang Gereja sebagai Komunitas Pembelajaran dan Pembinaan pada Masa Kini - Markus Tuhumury; Sang Putra Immanuel Duha; Jekson Tulus (Sekolah Tinggi Teologi Nusantara, 2024)
Social transformation due to technological advances have changed the way humans relate. Relationships can be developed more easily, cheaper and faster. As a community, the church is